Pemanfaatan Pendidikan Multikultural dalam Membentuk Sikap Toleransi Peserta Didik - Muhammad Ainur Rafiq; Sapuadi Sapuadi (JOURNAL SAINS STUDENT RESEARCH, 2026)
This study examines the role of multicultural education in shaping students’ tolerance attitudes in diverse societies. The research is motivated by the increasing cases of intolerance, discrimination, and social conflict in educational environments, which indicate the need for strengthening students’ understanding of diversity. The objective of this study is to analyze how multicultural education contributes to the development of tolerance among students. This research employs a qualitative approach using a literature review method by collecting and analyzing relevant scientific sources such as journals, books, and academic publications from the last decade. Data analysis is conducted through content analysis, including literature selection, data reduction, data presentation, and conclusion drawing. The findings reveal that multicultural education plays a significant role in fostering tolerance, empathy, and respect for differences among students. It not only enhances cognitive understanding of diversity but also develops affective and behavioral aspects, such as openness, cooperation, and social awareness. However, challenges remain, including limited teacher understanding, insufficient learning resources, and lack of policy support. The study implies that integrating multicultural education into curricula, classroom practices, and extracurricular activities is essential to create inclusive and harmonious educational environments. Therefore, multicultural education is a relevant and effective approach to building tolerant, humanistic, and socially responsible students in multicultural societies.